PROGNOSTIC CRITERIA FOR THE RISK OF BRONCHIAL ASTHMA IN CHILDREN WITH OBSTRUCTIVE BRONCHITIS - Panakhova, T.T. (World of Medicine and Biology, 2022)
The purpose of the study was to identify prognostic criteria for the formation of bronchial asthma in children with obstructive bronchitis. The material for the work included the data of a retrospective examination of 100 children with recurrent obstructive bronchitis aged from 1 to 7 years (the first group). The second group included 89 children diagnosed with bronchial asthma. All children underwent a comprehensive examination, including the copying of information from medical records, questioning of parents, analysis of risk factors, assessment of allergic history and examination of laboratory parameters. The diagnostic test for the absolute number of eosinophils showed high specificity of 84.9±4.9, and sensitivity of 63.6±14.5. The relative number of eosinophils showed high sensitivity and specificity: 81.8±5.2 and 84.1±4.0, respectively. Testing of immunoglobulin E showed absolute sensitivity of 100.0±0.0, specificity 72.2±7.5. Thus, high prognostic efficiency in the development of asthma in children with obstructive bronchitis has parental allergic diseases, urogenital infections and maternal preeclampsia during pregnancy, birth injury and asphyxia in the neonatal period, absolute and relative eosinophilia, hyperimmunoglobulinemia E.